(3GdCZPjI hGdCTQHI ddCUMGAs - (3eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO, GdfLjH GdSeQbfOj , J (B619 (3g` s ((3Rjf GdYGHOjf Hf eMeO HGHG afcQI s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Ef Gddg JYGdi deG Ndb fhY GdEfSGf CYOd eRGLkG ef LejY GdMjhGfGJ ,hLYd Pdc GdEYJOGd YQjVkG ZjQ eMUhQ s
(3BNQgG (B:s
(3hYfO GdVYa hGdYTi CcKQ hCTO ef ESJYeGd SGFQ GdQhGFM GdWHjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3fSNI SGOSI ef GdbSe GdQGHY ef GdfLjHjGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs